Growth of Salam (Syzygium polyanthum) to the Application of Cow Manure and Husk Charcoal on Used Oil Contaminated Soil - Basuki Wasis; Deni Prihanto (Jurnal Silvikultur Tropika, 2023)
Salam plant (Syzygium polyanthum) can grow in marginal soils, such as soil contaminated with used oil. The planting of salam with the application of cow manure and husk charcoal is expected to reduce the bad impact of used engine oil pollution. This study aims to analyze the response to the growth of salam and to obtain information on the optimal dose to increase the growth of salam to the application of cow manure and husk charcoal on soil contaminated used engine oil with a concentration of 60 ml/1 kg of soil. The study used a factorial completely randomized design with two factors and soil analysis test. The result showed that the application of cow manure and its interaction with husk charcoal significantly affected the root shoot ratio (NPA) parameter. The combination of 60 grams of cow manure and 60 grams husk charcoal had the best NPA value of 3,11. The high growth of salam tended to be optimal in the K4A0 treatment (dose of 120 gram of cow manure and 0 gram of husk charcoal). The application of treatment can reduce the Al, Zn, and Mn content in the contaminated with used engine oil. Keywords: cow manure, husk charcoal, root shoot ratio, Syzygium polyanthum, used engine oil